Integrating Problem Based Learning and Quizizz to Foster Learning Activeness in Elementary Science - Dedek Oktavia Nasution; Zurriana Nainggolan; Hamka (Al-Qalam Institute, 2026)
The Merdeka Curriculum envisions IPAS as an active, inquiry-based subject, yet lecture-dominated instruction in Indonesian elementary schools continues to produce passive learning and low student activeness. This study examined the effect of the Problem Based Learning (PBL) model assisted by Quizizz on the learning activeness of third-grade elementary students in the IPAS topic of changes in the state of matter. A quasi-experimental nonequivalent pretest-posttest control group design was employed with 52 third-grade students at SDN 088 Panyabungan, divided through total sampling into an experimental class (n = 26) and a control class (n = 26). Data on five activeness dimensions were collected through validated observation checklists and questionnaires and analyzed using an independent samples t-test. A statistically significant difference in learning activeness emerged between the groups (p < 0.05), with the experimental class achieving a medium normalized gain (N-Gain = 0.57) against a low gain (N-Gain = 0.24) in the control class, and the largest improvements appearing in the oral and emotional dimensions. The integration of PBL with Quizizz serves as a catalyst for transformational education, effectively shifting the pedagogical paradigm from passive knowledge consumption to the active construction of meaning while fostering the holistic learner agency essential to the Profil Pelajar Pancasila framework.